A value chain analysis of health insurance industry, government and healthcare providers in Indonesia - Isnalita, Noorlailie Soewarno, Bambang Tjahjadi, (Opción, 2019)
This study explores the value chain of the health insurance industry, government institutions, and healthcare providers in Indonesia. It is designed as qualitative research using exploratory case study approach. Primary data are obtained through in-depth interviews with informants consisting of health insurance managers, government officers, and hospital managers. Secondary data are collected through public reports. Some parties contribute to the high cost of healthcare in Indonesia along the value chain of the health insurance industry, government institutions, and healthcare providers. The structural cost drivers include bureaucracy, lack of synergy, fraud, hospital claims, medicine price, participants’ behavior, and insurance companies’ behaviors.